Dynamical behavior of Borospherene: A Nanobubble - Martinez-Guajardo, Gerardo; Luis Cabellos, Jose; Diaz-Celaya, Andres; Pan, Sudip; Islas, Rafael; Chattaraj, Pratim K.; Heine, Thomas; Merino, Gabriel (Scientific Reports, 2015)
The global minimum structure of borospherene (B40) is a cage, comprising two hexagonal and four heptagonal rings. Born-Oppenheimer Molecular Dynamics simulations show that continuous conversions in between six and seven membered rings take place. The activation energy barrier for such a transformation is found to be 14.3 kcal·mol-1. The completely delocalized σ - and π-frameworks, as well as the conservation of the bonding pattern during rearrangement, facilitate the dynamical behavior of B40. B40 is predicted to act as a support-free spherical two-dimensional liquid at moderate temperature. In other words, B40 could be called as a nanobubble.
CRIS-Team Scopus Importer:2023-03-20